2006
DOI: 10.1002/pmic.200500420
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the tegument and excretory-secretory products of adult Schistosoma bovis worms

Abstract: Schistosoma bovis is a ruminant pathogen that is poorly known at a molecular level. With an aim of identifying the parasite proteins involved in host-parasite interplay, we studied two protein extracts that contain, respectively, the proteins excreted/secreted by the adult worm (ES) and the tegumental proteins exposed to the host (TG). The 2-DE, 2-D immunoblot and MS were employed to separate and identify the antigenic proteins and the most abundant non-antigenic proteins in each extract. There were some 400 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 40 publications
3
77
1
1
Order By: Relevance
“…However, our study indicated it may be excreted or secreted into host serum (Table I); this result strongly argues against the possibility that SjFABP is unlikely to be accessible to the immune system (52). Furthermore the presence of FK506-binding protein in the adult worm ES proteome was also observed in Fasciola hepatica (29,30), S. bovis (33), and S. mansoni (34,35), suggesting that its secretion is conserved among trematodes. FABP from F. hepatica induces an immune response in mice that is protective to challenge infection with S. bovis cercariae (62), whereas FABP from S. mansoni induces immune protection against challenge with F. hepatica metacercariae and S. mansoni cercariae (62).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, our study indicated it may be excreted or secreted into host serum (Table I); this result strongly argues against the possibility that SjFABP is unlikely to be accessible to the immune system (52). Furthermore the presence of FK506-binding protein in the adult worm ES proteome was also observed in Fasciola hepatica (29,30), S. bovis (33), and S. mansoni (34,35), suggesting that its secretion is conserved among trematodes. FABP from F. hepatica induces an immune response in mice that is protective to challenge infection with S. bovis cercariae (62), whereas FABP from S. mansoni induces immune protection against challenge with F. hepatica metacercariae and S. mansoni cercariae (62).…”
Section: Discussionmentioning
confidence: 71%
“…As shown by immunoblotting, there were fewer immune antigenic proteins in ES product than in whole worm protein extracts, which is contrary to the notion that ESPs are exposed to the host immune system and enriched in antigenic proteins. This was also true for the ES and tegument proteome of S. bovis adult worms (33). One explanation for this phenomenon is that the challenged sera contained antibodies against ES proteins from eggs or schistosomula but minimal antibodies against the adult worms.…”
Section: Excretory/secretory Proteins Of Blood Flukementioning
confidence: 89%
See 1 more Smart Citation
“…Studies were also performed to explore the protein content of the tegument of the ruminant parasite S. bovis [50]. One of these studies used 2D immunoblots with infected sheep serum to identify the most antigenic proteins in the tegument preparation.…”
Section: Probing the Schistosome Surface By Proteomicsmentioning
confidence: 99%
“…The spots from a parallel 2D electrophoresis corresponding to those regions identified in the 2D immunoblot were excised and 5 different proteins were determined by mass spectrometry. All of those proteins are soluble and include orthologs of S. mansoni vaccine candidates glutathione-S-transferase and GAPDH [50]. Considering that the approach that has been utilized shows a very limited recovery of integral membrane proteins, it is understandable that only soluble proteins have been sampled.…”
Section: Probing the Schistosome Surface By Proteomicsmentioning
confidence: 99%